Dateneigentum - Weiß, Johannes (Mohr Siebeck, 2025)
Is there such a thing as ownership of data? Addressing the question of property rights to data from a far-reaching and multifaceted perspective, Johannes Weißs study takes its findings to justify their existence in the applicable legal system.
PublicationDate: 20250409
Keywords: Eigentum -- Daten -- Befugnisbündel -- Rechte an Daten -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht